Navigating Airway Management in Pseudo-Double Vocal Cord Anatomy: A Case Report - Rhendra Hardy Mohamad Zaini; Muhamad Aizuddin Bin Ismail (Bali Journal of Anesthesiology)
Pseudo-double vocal cord anatomy is a rare and challenging anomaly that can complicate airway management, requiring careful planning and precise execution. This report aims to expand the limited literature on this condition, discussing diagnostic complexities and strategies for successful airway management in such cases. A 65-year-old female presented with a pedunculated laryngeal mass, mimicking a second set of vocal cords, leading to significant diagnostic and procedural challenges. Preoperative evaluation, including flexible endoscopy and computed tomography imaging, revealed a lesion originating from the aryepiglottic fold, narrowing the hypopharyngeal lumen. Awake fiberoptic intubation using a pediatric bronchoscope and laser-resistant endotracheal tube ensured patient safety and procedural success. Surgical debulking of the mass was performed, and histopathological examination confirmed the presence of a benign lesion. The patient’s preference to avoid a tracheostomy was respected, highlighting the importance of shared decision-making in clinical care. This case emphasizes the value of multidisciplinary collaboration, advanced airway management techniques, and patient-centered care in addressing complex airway anomalies. It contributes to the understanding of pseudo-double vocal cord anatomy, offering practical insights for clinicians managing similar scenarios.